PENGARUH DOSIS UREA-HUMAT TERHADAP KETERSEDIAAN N PADA ENTISOL DAN SERAPAN N OLEH TANAMAN JAGUNG - Yerli Yuspita Tampubolon; Retno Suntari (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2017)
The constrains of corn cultivation on Entisol is due to the low nutrient absorption, one of this element is Nitrogen. The reason is Nitrogen can easily for leached from the soil in the form of nitrate (N-NO3-), and will volatilized into the air in the form of ammonia gas (NH3) or left in the ground so it can't be absorbed by plants. One effort that can be done to address the problems ofÂ Entisol is with the addition of organic matter as well as a balance fertilizer. Organic ingredients are used in the research is mixed with humic acid with urea. This study was aimed to examine the influence of application of urea-humate dosage on N availability and uptake of N of corn. The results showed a significant effect of application of urea-humate to NH4+ and NO3- at 30 DAI. The urea-humic acid could improve soil pH, soil CEC, plant height, and total dry weight. Correlation between soil N-available level with uptake of N level was significant at p = 0,05 (r = 0,81). Urea humate 125% has the highest increase of 49,32% on N-uptake of corn compared with the treatment of urea